Effect of Fe substitution by Co on off-stoichiometric Ni–Fe–Co–Mn–Sn Heusler alloy ribbons. (11th August 2017) - Mishra, S S; Mukhopadhyay, Semanti; Yadav, T P; Yadav, R M; Radhakrishnan, Sruthi; Vajtai, R; Ajayan, P M; Mukhopadhyay, N K; Singh, H K; Srivastava, O N
Abstract: We have synthesized Ni45 Fe5− X Co X Mn40 Sn10 Heusler alloy with different Co doping and studied the effect on the structural and magnetic properties of Ni45 Fe5− X Co X Mn40 Sn10 (at. X = 0, 2.5, 5) ribbons. X-ray diffraction, scanning and transmission electron microscopic characterization reveal the structural/microstructural features in melt-spun ribbons of different compositions. A significant transformation in the crystal structure has been observed in Fe substituted ribbons. The crystal structure changes from cubic L21 phase to bi-phasic 4O + L21 and 10M + L21 modulated phases for the partial and complete substitution of Fe by Co specimens respectively. Williamson–Hall analysis of x-ray diffraction data was used to compute the crystallite size and residual elastic strain. Magnetic properties and magnetic field-induced structural transformation of melt-spun alloy ribbons over a large temperature range of 10 K ⩽ T ⩽ 500 K were examined. Our results revealed that Fe substitution by Co causes a change in the magnetic behavior which could be ascribed to the increase in the lattice strain as well as a magnetic strain due to high antiferromagnetic fraction.